3D assembly of Ti3C2-MXene directed by water/oil interfaces. Issue 8 (19th January 2018) - Bian, Renji; Lin, Ruizhi; Wang, Guilin; Lu, Gang; Zhi, Weiqiang; Xiang, Shanglin; Wang, Tingwei; Clegg, Paul S.; Cai, Dongyu; Huang, Wei
Abstract : An interfacial route is demonstrated for assembling 2D Ti3 C2 -MXene into 3D architectures. Abstract : MXene is an emerging class of 2D materials exfoliated from ternary carbide and nitride ceramics. The exfoliation process, which is an acid etching approach, functionalizes the MXene surface with –OH, –O and –F groups. These functional groups offer significant opportunities for tuning the colloidal properties of the MXene nanoblocks; importantly, this tunability points the way towards a facile route for assembling these nanoblocks into 3D architectures that are in demand for many applications. This route, presented for the first time here, uses water/oil interfaces for assembling Ti3 C2 -MXene in 3D architectures. It shows that cetyl trimethylammonium bromide (CTAB) can be used to tune the hydrophilic–hydrophobic balance of Ti3 C2 -MXene via the interaction of positively charged –N(CH3 )3 and –O groups on the MXene surface. Crucially, it is found that this interaction can be controlled via the hydrogen ion concentration in the aqueous phase. Stable oil-in-water emulsions are the only product when the aqueous phase is neutral or basic. This understanding led us to fabricate a high internal phase Pickering emulsion with more than 70 vol% oil droplets and also a solid porous monolith based on this emulsion template.